“Étrangers à la montagne” - Aimada Solé; Miguel Solana; Enric Mendizabal (Revue de Géographie Alpine)
This article explores the social and cultural integration of international labour migrants to a mountain area, the High Pyrenees and Aran (Catalan Pyrenees, Spain). Since the last two decades of the 20th century, the Pyrenees has experienced significant social and economic changes. Until then, demographic, social and economic indicators showed mountain rural areas as marginal spaces characterized by deep economic crisis, a significant demographic recession and an important decrease in traditional activities. Nevertheless, from the nineties onwards we observe a demographic recovery in the Pyrenees. This new trend is caused by positive net migration, especially international labour migration. In order to understand some of the impacts of the new arrivals of international immigrants, this article focuses on the process of integration. In so doing we attempt to investigate three key issues in social and cultural integration: social interaction with local people, community participation and membership in associations. The small size of villages and towns and the lack of privacy are characteristic of this mountain area. Some migrants consider this a positive aspect, in the sense that they are less likely to be categorized as the foreigner. Others say that the small size requires more fences, more barriers, and this hampers relationships.